1997
DOI: 10.1073/pnas.94.9.4610
|View full text |Cite
|
Sign up to set email alerts
|

A cholera toxoid-insulin conjugate as an oral vaccine against spontaneous autoimmune diabetes

Abstract: Mucosally induced immunological tolerance is an attractive strategy for preventing or treating illnesses resulting from untoward inf lammatory immune reactions against self-or non-self-antigens. Oral administration of relevant autoantigens and allergens has been reported to delay or suppress onset of clinical disease in a number of experimental autoimmune and allergic disorders. However, the approach often requires repeated feeding of large amounts of tolerogens over long periods and is only partly effective i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
183
1
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(190 citation statements)
references
References 41 publications
5
183
1
1
Order By: Relevance
“…administration of OVA/CTB conjugate effectively induces OVA-specific peripheral immunological tolerance, whether tested in normal BALB/c mice, OVA TCR Tg (DO11.10) mice, or in either BALB/c mice or Rag1 Ϫ/Ϫ mice transferred with OVA TCR Tg T cells. Consistent with our previous findings in other systems (17)(18)(19)(20)(21)(22), oral tolerance induction with Ag/CTB conjugate was superior to that induced with free Ag both in markedly increasing the efficacy of tolerization and in dramatically decreasing the effective amounts of Ag. The oral tolerance by i.g.…”
Section: Discussionsupporting
confidence: 91%
“…administration of OVA/CTB conjugate effectively induces OVA-specific peripheral immunological tolerance, whether tested in normal BALB/c mice, OVA TCR Tg (DO11.10) mice, or in either BALB/c mice or Rag1 Ϫ/Ϫ mice transferred with OVA TCR Tg T cells. Consistent with our previous findings in other systems (17)(18)(19)(20)(21)(22), oral tolerance induction with Ag/CTB conjugate was superior to that induced with free Ag both in markedly increasing the efficacy of tolerization and in dramatically decreasing the effective amounts of Ag. The oral tolerance by i.g.…”
Section: Discussionsupporting
confidence: 91%
“…9), an immune-modulatory agent (30,31). Coupled to relevant auto antigens, CTB has been shown to effectively prevent the development of T cell-mediated autoimmune diseases, including encephalomyelitis, arthritis, and type I diabetes, in animal models (32)(33)(34). Recently, it has been reported that pretreatment of macrophages and monocytes with CTB diminishes the LPS-induced proinflammatory response, leading to a significant decrease in the production of TNF-␣ and IL-6 (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in addition to functioning as a carrier for the cholera toxin A subunit to target adenylate cyclase, CTB can exert immune-modulating effects independent of the A subunit (30,31). CTB has been reported to suppress the onset of T cell-dependent autoimmune diseases and to potentiate tolerance of the adaptive immune response (32)(33)(34). Pretreatment of macrophages with CTB has been reported to suppress the LPS-induced production of TNF-␣ and IL-6 (30, 31).…”
Section: Mkp-1 Is Induced By the Immune-modulatory Agents Dexamethasomentioning
confidence: 99%
“…As the addition of oral insulin does not influence metabolic control, higher doses of oral insulin should possibly be tested. The use of an adjuvant carrier to increase the tolerogen capacity of insulin is also worth consideration for tolerance induction, with implications for clinical use [15].…”
Section: Discussionmentioning
confidence: 99%